A diary study of work consequences for hotel employees victimized by supervisor from a demand-resource perspective on employee emotions. (January 2021) - Park, In-Jo; Kim, Peter Beomcheol; Jung, Heajung; Yun, Dongwon; Hai, Shenyang
Highlights: This research examines how hotel employees' perceived victim identity influences their daily work attitudes using a diary study method. The effects of employees' perceived victim identity on daily job satisfaction and daily work engagement are mediated by their emotional change. Employees' level of emotional exhaustion exacerbates the negative relationships between their emotional change and daily work attitudes. The role of emotional change and emotional exhaustion can be explained by a demand-resource perspective on employee emotions. Abstract: How would perceiving oneself as a victim of abusive supervisor behavior affect one's work attitudes? This study examines the mediating role of emotional change on the detrimental work outcomes caused by hotel employees' perceived victim identity. It further investigates how emotional exhaustion moderates the relationship between perceived victim identity and two outcome variables, daily job satisfaction and work engagement. The research hypotheses were tested by a multi-level analysis (cf., hierarchical linear modeling) using a sample of 128 hotel employees in China who took surveys twice per day over 14 consecutive days. The findings show that emotional change significantly mediates the negative effect of hotel employees' perceived victim identity on their work attitudes, and emotional exhaustion moderates this effect such that higher exhaustion exacerbates the negative relationship. Theoretical and practical implications of the findings for hospitality researchers and practitioners are discussed.